Proposta de um modelo integrado para avaliação dos riscos digitais no contexto da transformação digital em indústrias - Santos Filho, Vitor Hugo dos (2024)
Digital transformation has been redefining the production and operational processes of organizations. On one hand, Industry 4.0 emphasizes automation and connectivity between systems and machines to optimize efficiency, while Industry 5.0 fosters a more humancentered approach, enhancing collaboration between technologies and workers. However, this transformation also introduces significant challenges, such as information overload, increasing internet dependency, cybersecurity vulnerabilities, and other emerging risks. This study stems from the identification of gaps in literature, where risk assessment models remain incipient and insufficiently explored, leading to uncertainty regarding the actual impacts of digital transformation. In this context, the objective of this study was to develop an integrated model for assessing digital risks within the framework of digital transformation in industries. This study aims to propose an integrated model for assessing digital risks in the context of digital transformation in industries (Integrated Model of Digital Risks in Digital Transformation - IMRDDT). To achieve this goal, a systematic literature review was initially conducted, enabling the identification and categorization of these digital risks. Based on this foundation, a theoretical model comprising 11 dimensions and 49 digital risks was developed. From these dimensions and variables, a research instrument was designed to measure and evaluate digital risks, as well as their potential impact on industries. The model was validated in 62 industries across different segments. Through the application of the research instrument, digital risk maps were constructed, associating risk impacts with the implementation of digital transformation. The analysis revealed the probability levels of risk occurrence in each of the 62 industries, showing that 8 industries were at level 2 (low probability), 28 at level 3 (moderate probability), and 26 at level 4 (high probability). Statistically, the model's consistency was validated using Cronbach's Alpha Test, while the Fuzzy Delphi method was employed to achieve expert consensus on digital risks. Additionally, 150 mitigation actions were proposed for the set of 49 digital risks. A digital tool in the form of a dashboard was also developed to facilitate data interpretation and analysis, contributing to strategic decisionmaking. The model developed in this study can serve as a diagnostic tool for companies to identify the highest probabilities of digital risk occurrences and assess their potential impacts. Furthermore, the model can support companies in preparing for the challenges of digital transformation within the industrial context.